Aplicação de polieletrólitos para a separação de metais em efluentes da suinocultura - Steinmetz, Ricardo Luis Radis (2007)
The increase on swine livestock activity demands profitable resources and environmentally sustainable for the treatment, disposal and the residual water reuse. Due to the high wastewater volume, they have a huge pollutant load, among them several metals, that can cause environment impact. This work presents an evaluation of phase separation for Al, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, Sr and Zn removal in swine manure through the coagulation and flocculation whit synthetic and natural polyelectrolyte. For this proposal, the metals were monitored in the effluent and solid-liquid separation assays (Jar Test) with poliphenolic polymer (Tannin) and polyacrilamide (PAM) applied at different concentration. The optimization was accomplished by the application of factorial design. For the metal determination three mixtures of reagents had been evaluated (nitric acid + perchloric acid, sulfuric acid + hydrogen peroxide and nitric acid + hydrogen peroxide) for samples decomposition of swine manure, the best result for recovery and correlation was found to nitric acid and hydrogen peroxide mixture. After the separation of the liquid fraction, reductions between 68 and 99% were found out in the investigated metal concentrations. Besides that, reductions over 90% for chemical oxygen demand were also observed. A significant influence in turbidity removal only by the tannin utilization was found out. However the PAM application improved directly the flocks generation and influenced the sludge volume reduction. The polyelectrolyte use provided the reduction of metal concentration in the wastewater to adjust to the brazilian legislation for discharging into water bodies or for reuse in irrigation systems. The sludge produced after the solid-liquid separation also showed concentrations of inorganic constituents below of maximum limits claimed by legislation for the agricultural use.